Remarks on the nomenclature of Anthurium ×macrolobum (Araceae) - Nachychko, Viktor O.; Sosnovsky, Yevhen V.; Prokopiv, Andriy I. (Phytotaxa, 2021)
The paper presents a detailed nomenclatural study of the name Anthurium ×macrolobum, an accepted artificial hybrid between A. leuconeurum and A. pedatoradiatum, which is a popular ornamental houseplant cultivated around the world. Nomenclatural confusion was found to be associated with the valid publication of A. ×macrolobum, and a binding decision of the General Committee for Botanical Nomenclature is required. Furthermore, since A. ×macrolobum was published six years later than the name A. ×dentatum by Devansaye (1883 vs. 1877) for the same hybrid, it has to be superseded by the latter name according to the priority principle. However, the name proposed in 1877 has never been used, and its later isonym (A. ×dentatum by André, published in 1884) has been traditionally treated as a taxonomic synonym of A. ×macrolobum. Therefore, for preserving the standing application of the name A. ×macrolobum, its conservation against of A. ×dentatum by Devansaye is desirable. Neotypes for both A. ×macrolobum and A. ×dentatum by Devansaye are designated in the present paper.